2020
DOI: 10.1523/eneuro.0218-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Turning the Stimulus On and Off Changes the Direction of α Traveling Waves

Abstract: Traveling waves have been studied to characterize the complex spatiotemporal dynamics of the brain. Several studies have suggested that the propagation direction of α traveling waves can be task dependent. For example, a recent electroencephalography (EEG) study from our group found that forward waves (i.e., occipital to frontal, FW waves) were observed during visual processing, whereas backward waves (i.e., frontal to occipital, BW waves) mostly occurred in the absence of sensory input. These EEG recordings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 36 publications
(59 reference statements)
5
29
0
Order By: Relevance
“…All in all, we could confirm our previous conclusion that covert visual attention modulates top-down oscillatory waves, showing this effect even in the absence of visual stimulation. In addition, we surmised that the lateralization effect we reported in the forward waves in our dataset (absent in the Foster dataset) is related to the steady visual stimulation during the attentional allocation, in line with our previous results demonstrating that oscillatory bottom-up waves reflect sensory processing ( Alamia and VanRullen, 2019 ; Pang et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…All in all, we could confirm our previous conclusion that covert visual attention modulates top-down oscillatory waves, showing this effect even in the absence of visual stimulation. In addition, we surmised that the lateralization effect we reported in the forward waves in our dataset (absent in the Foster dataset) is related to the steady visual stimulation during the attentional allocation, in line with our previous results demonstrating that oscillatory bottom-up waves reflect sensory processing ( Alamia and VanRullen, 2019 ; Pang et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…However, before testing how visual attention modulates traveling waves, we explored the amount of waves propagating forward (FW) and backward (BW) as a function of their temporal frequency (see Figure 5 and methods for a detailed description of the analysis). Figure 1D shows the spectral profile of FW and BW waves in the midline (along the Oz–Fz axis) and the contra- and ipsilateral lines: confirming previous experimental studies ( Alamia and VanRullen, 2019 ; Pang et al, 2020 ), we found that alpha-band oscillatory waves propagate in both directions during visual stimulation, whereas theta (4–7 Hz) and high-beta/gamma (24–45 Hz) bands propagate mostly bottom-up from occipital to frontal regions, and low-beta (13–23 Hz) waves flow in the top-down direction. Interestingly, this pattern of results confirms previous studies using different methods, in which higher frequency bands (i.e., high-beta/gamma) have been associated with forward processing, whereas low-beta and alpha frequencies have been related to top-down processing ( Bastos et al, 2012 ; Bastos et al, 2015 ; van Kerkoerle et al, 2014 ; Michalareas et al, 2016 ; but see also Schneider et al, 2021b ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations